Serum concentrations of cholesterol, apolipoprotein A-I and apolipoprotein B in a total of 1694 meat-eaters, fish-eaters, vegetarians and vegans. - Bradbury, K; Bradbury, K; Crowe, F; Appleby, P; Schmidt, J; Travis, R; Key, T (2014)
BACKGROUND/OBJECTIVES: The objective of this study was to describe serum lipid concentrations, including apolipoproteins A-I and B, in different diet groups. SUBJECTS/METHODS: A cross-sectional analysis of a sample of 424 meat-eaters, 425 fish-eaters, 423 vegetarians and 422 vegans, matched on sex and age, from the European Prospective Investigation into Cancer and Nutrition-Oxford cohort. Serum concentrations of total, and high-density lipoprotein (HDL) cholesterol, as well as apolipoproteins A-I and B were measured, and serum non-HDL cholesterol was calculated. RESULTS: Vegans had the lowest body mass index (BMI) and the highest and lowest intakes of polyunsaturated and saturated fat, respectively. After adjustment for age, alcohol and physical activity, compared with meat-eaters, fish-eaters and vegetarians, serum concentrations of total and non-HDL cholesterol and apolipoprotein B were significantly lower in vegans. Serum apolipoprotein A-I concentrations did not differ between the diet groups. In males, the mean serum total cholesterol concentration was 0.87 nmol/l lower in vegans than in meat-eaters; after further adjustment for BMI this difference was 0.76 nmol/l. In females, the difference in total cholesterol between these two groups was 0.60 nmol/l, and after further adjustment for BMI was 0.55 nmol/l. CONCLUSIONS: In this study, which included a large number of vegans, serum total cholesterol and apolipoprotein B concentrations were lower in vegans compared with meat-eaters, fish-eaters and vegetarians. A small proportion of the observed differences in serum lipid concentrations was explained by differences in BMI, but a large proportion is most likely due to diet.